Café-Relevant Value and Brand Awareness on Purchase Intention: Empirical Study of Local Brand Cafe - Roymon Panjaitan; Edwin Zusrony (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2022)
The importance of this study is discussed to determine the intensity of purchases resulting from cafe-relevant value, as well as the impact of brand awareness through e-wom. Two hundred forty-six respondents were used as coffee lovers in cafes, most used questionnaires and interviews as data collection methodologies. This study analyzed data from e-WOM-mediated path analysis on purchase intention using SEM-PLS multiple path analysis. The research findings have a positive relationship between cafe relevant value and brand awareness in influencing e-wom and a direct positive contribution between café-relevant value and brand awareness on purchase intention. So, it is proven that e-wom has the potential to increase the intensity of coffee purchases in cafes.